2012
DOI: 10.1121/1.3670594
|View full text |Cite
|
Sign up to set email alerts
|

Sine-wave speech recognition in a tonal language

Abstract: It is hypothesized that in sine-wave replicas of natural speech, lexical tone recognition would be severely impaired due to the loss of F0 information, but the linguistic information at the sentence level could be retrieved even with limited tone information. Forty-one native Mandarin-Chinese-speaking listeners participated in the experiments. Results showed that sine-wave tone-recognition performance was on average only 32.7% correct. However, sine-wave sentence-recognition performance was very accurate, appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…In the sine-wave replicas, the speech signals were reduced to only three sinusoids that follow the contours of the first three formants of the speech (Remez et al, 1981). While the tone recognition scores of the sine-wave replicas of Chinese monosyllables were just slightly above chance, sentence recognition of the sine-wave replicas was nearly perfect (Feng et al, 2012). Thus, it seems that lexical tone is not important for sentence recognition in Mandarin Chinese.…”
Section: Introductionmentioning
confidence: 88%
“…In the sine-wave replicas, the speech signals were reduced to only three sinusoids that follow the contours of the first three formants of the speech (Remez et al, 1981). While the tone recognition scores of the sine-wave replicas of Chinese monosyllables were just slightly above chance, sentence recognition of the sine-wave replicas was nearly perfect (Feng et al, 2012). Thus, it seems that lexical tone is not important for sentence recognition in Mandarin Chinese.…”
Section: Introductionmentioning
confidence: 88%
“…The lack of ecological validity of the materials may limit the explanation of our results. However, in a recent study, Feng et al (2012) found that although lexical tone recognition for sine-wave Chinese monosyllabic words is poor, the recognition accuracy for sine-wave sentences is very high, reflecting the compensation effect of contextual information when the tonal information is poor. Our results, together with the findings of Feng et al (2012), indicate that the functional load of lexical tones on sentence comprehension is limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study, Feng et al (2012) found that although lexical tone recognition for sine-wave Chinese monosyllabic words is poor, the recognition accuracy for sine-wave sentences is very high, reflecting the compensation effect of contextual information when the tonal information is poor. Our results, together with the findings of Feng et al (2012), indicate that the functional load of lexical tones on sentence comprehension is limited. That is, lexical meaning access is possible in a sentence context when surface pitch patterns of tones are altered, although lexical tones are as important as segmental phonemes in specifying the meaning of a word in a tone language.…”
Section: Discussionmentioning
confidence: 99%
“…Other acoustic cues known to be important for speech understanding, e.g., harmonic structure and fundamental frequency (F0) contour, are discarded during this processing. Feng et al reported the recognition performance of Mandarin SWS and found that Mandarin-speaking listeners could receive a high recognition rate for sine-wave sentences [1]. Sine-wave based speech synthesis has provided a useful framework to study the importance of formants to speech recognition [e.g., 1,2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al reported the recognition performance of Mandarin SWS and found that Mandarin-speaking listeners could receive a high recognition rate for sine-wave sentences [1]. Sine-wave based speech synthesis has provided a useful framework to study the importance of formants to speech recognition [e.g., 1,2,3]. However, some questions remain regarding the contribution of formant information in SWS recognition.…”
Section: Introductionmentioning
confidence: 99%